The Filatov’s Palette (Ukrainian Journal of Ophthalmology, 2025)
We hope that for our readers a new section, The Filatov’s Palette, will become a source of new knowledge that will facilitate findings of the wonderful aspects of Volodymyr Petrovych Filatov’s personality, and enable enjoying the atmosphere of relationships between the persons that were influencing in some way the formation of his life line. While paying homage to forerunners and pioneers, we believe it is appropriate or necessary to let the journal cover the circumstances and events related also to our contemporaries who are guided by the examples of Filatov’s closest colleagues while trying to multiply their original talents.